2010
DOI: 10.1523/jneurosci.3383-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Synaptic Modulation on β-Amyloid, Synaptophysin, and Memory Performance in Alzheimer's Disease Transgenic Mice

Abstract: Accumulation of ␤-amyloid (A␤) and loss of synapses are hallmarks of Alzheimer's disease (AD). How synaptic activity relates to A␤ accumulation and loss of synapses is a current topic of major interest. Synaptic activation promotes A␤ secretion, and chronic reduction of synaptic activity reduced A␤ plaques in an AD transgenic mouse model. This suggested beneficial effects of reducing synaptic activity in AD. We now show that reduced synaptic activity causes detrimental effects on synapses and memory despite re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 38 publications
4
97
1
Order By: Relevance
“…Here, we present evidence that glutamate itself, after Aβ-induced release from astrocytes, is responsible, at least in part, for triggering synaptic loss. Additionally, the effect of eNMDAR vs. sNMDAR activity on Aβ production and oligomerization (7,8,59,60) could produce a positive feedback loop whereby oligomerized Aβ induces eNMDAR activity, as shown here, and eNMDAR activity also triggers toxic Aβ generation (Fig. 7G).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Here, we present evidence that glutamate itself, after Aβ-induced release from astrocytes, is responsible, at least in part, for triggering synaptic loss. Additionally, the effect of eNMDAR vs. sNMDAR activity on Aβ production and oligomerization (7,8,59,60) could produce a positive feedback loop whereby oligomerized Aβ induces eNMDAR activity, as shown here, and eNMDAR activity also triggers toxic Aβ generation (Fig. 7G).…”
Section: Discussionmentioning
confidence: 70%
“…Although this paradigm first was demonstrated for ischemic brain disease, accumulating evidence suggests that it also is true for neurodegenerative disorders involving protein misfolding, such as Huntington disease (3,4) and AD (7,8,59,60). Additionally, linking this dichotomy of eNMDAR vs. sNMDAR activation to synaptic integrity, we and others previously have shown that low levels of glutamate or endogenous synaptic activity may enhance dendritic spine growth (61,62).…”
Section: Discussionmentioning
confidence: 90%
“…Sleep deprivation, potentially via elevated synaptic activity, led to greater plaque pathology in AD transgenic mice [33], although intraneuronal Aβ, synapses or behavior were not examined in this study. On the other hand, diminished cerebral activity reduced plaque pathology but elevated intraneuronal Aβ and worsened synapse damage and behavioral impairment in AD transgenic mice [27]. Overall, these studies and the study by Mohajeri et al [28] support that either elevated or reduced cerebral activity can be detrimental to synapses via intraneuronal but not plaque-associated Aβ in AD transgenic mice.…”
Section: Figmentioning
confidence: 71%
“…Increasing evidence shows that amyloid plaques themselves are not the critical element in synapse damage, since unilateral inhibition of cortical activity in the barrel cortex of AD transgenic but not wild-type mice after whisker removal led to synapse degeneration despite plaque reduction but concomitant intraneuronal Aβ42 accumulation [27]. Similarly, excessive cerebral activity from seizures led to neurodegeneration accompanied by intraneuronal Aβ accumulation in AD transgenic compared to wild-type mice [28].…”
Section: Figmentioning
confidence: 99%
“…Both in vitro and in vivo reports have displayed that the accumulation of intracellular Aβ precedes the build up of extracellular deposits [134] and AD transgenic mice studies have reported a correlation between levels of intracellular Aβ and Aβ-related synapse damage and memory impairment. A correlation that was not observed with plaque burden [136]. It has been widely accepted that various oligomers are the most toxic assembly form responsible for pathology.…”
Section: Intracellular Aβ Toxicitymentioning
confidence: 90%